Composing A Suitable Family Constitution as Governance System of Rajawali Mas - Ivance Irawan (Fakultas Bisnis, 2023)
The purpose of the study is to compose a suitable family constitution that can be accepted by all stakeholders of Rajawali Mas, which are the family members of Rajawali Mas. Accepted family constitution can be measured by how the main stakeholder or the first generation of Rajawali Mas is willing to implement it. This study uses a qualitative research method with a case study approach. This study uses the first generation and the second generation of Rajawali Mas who join the business as the internal informants, and benchmark company, expert in human resource, psychologist, and law as the supporter informants (external). The data collection in this study is carried out through interview, observation, and documentation. Furthermore, legislation and legal form of the family constitution of the previous family business or past research on it, will be used to support the composition of family constitution for this research. This study concludes that the proposed Family Constitution in this research is based on the results of in-depth interviews with internal parties as members of the Rajawali Mas family. Therefore, the model offered by the researcher is in accordance with the dynamics of the Rajawali Mas family and business. The results show three main aspects: family, ownership and business. The family constitution then consists of 16 articles that all members of Rajawali Mas family should use as a guide to run its business. However, the Family Constitution model offered in this study is a draft, whereby the management of Rajawali Mas can make changes, additions, or subtractions to the points contained in each article of this Family Constitution.